Navigating the Spoken–Written Divide: Senior High School Teachers’ Perceptions of Teaching Speaking through the Genre-Based Approach - Nabila Hasri Ainun; Aksendro Maximilian (English Language Education Study Program, 2026)
The Genre-Based Approach (GBA), long embedded in Indonesia’s English curriculum and still conceptually retained under the Merdeka Curriculum’s text-type competencies, is widely associated with the teaching of writing, leaving its application to speaking comparatively under-examined. This qualitative case study investigates how two experienced English teachers in a state senior high school in Bandar Lampung perceive and enact GBA in teaching speaking, with particular attention to an issue rarely addressed in prior GBA research: teachers’ awareness of the distinction between spoken and written text. Data were collected through semi-structured interviews, transcribed, and analyzed thematically following an inductive-deductive coding process. Five themes emerged: teachers’ conceptual understanding of GBA, their enactment of the four-stage teaching–learning cycle in speaking lessons, their awareness of the spoken–written text distinction, their perceived effectiveness of GBA for developing speaking, and the contextual challenges they faced. Findings reveal that although both teachers grasped the basic principles of GBA and implemented its four stages, they diverged markedly in their sensitivity to spoken-mode features: one teacher defaulted to written-text-like, rehearsed speech due to perceived student limitations, while the other deliberately cultivated spontaneous, interactive talk. This asymmetry suggests that procedural familiarity with GBA does not guarantee a genre-appropriate treatment of spoken discourse. The study contributes a mode-awareness lens to GBA teacher-cognition research and offers implications for teacher professional development under the Merdeka Curriculum.